1992
DOI: 10.1073/pnas.89.14.6378
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression of mammalian type A gamma-aminobutyric acid receptors in mouse cells: demonstration of functional assembly of benzodiazepine-responsive sites.

Abstract: The differential sensitivity of type A -aminobutyric acid (GABAA) receptors to benzodiazepine lgands seen in the malian nervous system is thought to be generated by the existence of a number of different receptor subtypes, assembled from a range of closely related subunits (a1-6, P1-3, V1-3, and 6) encoded by discrete genes. The characteristics of a given subtype can be determined by the coexpression ofcloned cDNAs encoding the subunits ofinterest. Two transient expression systems have so far been employed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Together, these results demonstrate that Q67 and S68 within the ␣1 subunit are critical in mediating assembly with ␤3 to form 9S complexes, representing functional cell surface receptors (Mamalaki et al, 1987(Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). (9E10) ␣1 (HY) subunits appear to oligomerize less efficiently with (FL AG) ␤3 compared to (9E10) ␣1 and are rapidly degraded as previously described for unassembled wild-type ␣1 subunits (Gorrie et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitmentioning
confidence: 64%
See 1 more Smart Citation
“…Together, these results demonstrate that Q67 and S68 within the ␣1 subunit are critical in mediating assembly with ␤3 to form 9S complexes, representing functional cell surface receptors (Mamalaki et al, 1987(Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). (9E10) ␣1 (HY) subunits appear to oligomerize less efficiently with (FL AG) ␤3 compared to (9E10) ␣1 and are rapidly degraded as previously described for unassembled wild-type ␣1 subunits (Gorrie et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitmentioning
confidence: 64%
“…Quantitation of the gradients revealed that both proteins exhibited 9 S sedimentation coefficients, as previously described for functional GABA A receptors composed of ␣␤ or ␣␤␥ subunits (Fig. 6 A,B; Mamalaki et al, 1987Mamalaki et al, , 1989Hadingham et al, 1992;Gorrie et al, 1997;Tretter et al, 1997). In contrast, unassembled ␣ or ␤ subunits have 5 S sedimentation coefficients (Gorrie et al, 1997;Tretter et al, 1997).…”
Section: Reduced Oligomerization Of (9e10) ␣1 (Hy) With the ␤3 Subunitmentioning
confidence: 77%
“…The bovine r,l, fll,72L and 72S cDNAs have been described previouqy [l, 12,24]. cRNA was prepared from 0tl and fll ¢DNAs a~ prev.…”
Section: Methodsmentioning
confidence: 99%
“…a) One group included compounds with selective affinity, including the imidazopyridine zolpidem and triazolopyridazine CL218,872, ligands that selectively bind to GABA A -␣ 1 receptors. These compounds selectively potentiate the effect of GABA at GABA A -␣1 receptors, although this is concentration-dependent (i.e., they only show 10 -20-fold affinity selectivity for GABA A -␣ 1 receptors over GABA A -␣ 2 or -␣ 3 receptors), despite Ͼ1000-fold selectivity over GABA A -␣ 5 receptors (Hadingham et al, 1992;Faure-Halley et al, 1993;Sieghart, 1995). To add to the complexity, zolpidem has highintrinsic efficacy at GABA A -␣ 1 receptors, whereas CL218,872 displays reduced efficacy at this receptor; i.e., CL218,872 is a partial agonist at GABA A -␣ 1 receptors.…”
mentioning
confidence: 99%